Visionary Leadership In Improving The Quality Of Education - Agustin Wahyuningtyas; Ernani Hadiyati; M. Jamal Abdul Nasir (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
This study aims to analyze visionary leadership strategies in improving the quality of education. This research was conducted at Permata Mojokerto Integrated Islamic Junior High School, East Java. This study uses a qualitative research approach. The informants are the Head of Education of YPM, the vice principal, teachers and the committee/parents of students. The results of the study concluded that visionary leadership at SMPIT Permata Mojokerto, East Java is as follows: as a direction determinant by doing several ways, namely: sharing sessions, developing strategies, making changes, enabling and empowering, motivating and inspiring, collaborating and being role models, so that visionary leadership is able to make strategies in improving the quality of education, namely: human resource development, strengthening the role of parents,  curriculum development and fulfillment of adequate infrastructure. In the end, visionary leadership produces activities including improving the quality of human resources for educators and education personnel, improving the quality of graduates and effective and varied learning methods, as well as fulfilling adequate infrastructure